Workplace environment and nurse performance: Evaluating the mediating role of self-efficacy in hospital settings - Fathiyah Ma'ani; Josephina Agung; Yolla Margaretha; Bram Hadianto (Nursing and Health Sciences Journal (NHSJ), 2026)
Sustaining high-level nursing performance in complex hospital environments remains a critical determinant of healthcare delivery, clinical safety, and patient recovery outcomes. This empirical investigation evaluates the structural causal relationships among workplace environment, self-efficacy, and nurse performance within hospital settings, specifically analyzing the mediating role of self-efficacy. Data collection occurred in November 2025 at two selected healthcare facilities in Indonesia: Sumber Kasih Hospital in Cirebon and Budi Agung Juwana Hospital in Pati. Target sample size parameters were determined utilizing the Isaac and Michael formula, with a non-probability snowball sampling strategy yielding 208 completed nurse responses. Analytical procedures employed Covariance-Based Structural Equation Modeling to execute rigorous measurement validation, path analysis, and structural equation testing. Empirical findings demonstrate that both self-efficacy and the workplace environment have significant, direct positive effects on nurse performance. The quality of the workplace environment also exerts a strong, direct positive effect on nurses' self-efficacy. Mediation analysis confirms that self-efficacy partially mediates the relationship between the workplace environment and clinical performance outcomes. Multidimensional environmental support, encompassing physical gratification, psychological stability, independent competence, collaborative relationships, and structural supports, facilitates the execution of daily tasks while fundamentally reshaping nurses' perceptions of their clinical capabilities. Strengthening internal confidence enables nursing staff to maintain high standards of care under demanding operational conditions. Hospital administrators must combine structural environmental investments with psychological empowerment initiatives to optimize overall clinical care quality.